Monitoring of Background Radiation and Dose Rates inLibraries: Results from the University City of the UniversidadNacional Mayor de San Marcos in Lima, Peru - Villarreyes, Eduardo (2024)
Detailed measurements of background radiation in counts per minute (cpm) and dose rates (µSv/h) have been conducted in all the libraries of the National University of San Marcos, located in the University City of Lima, Peru. Radiation measurements were carried out using Geiger-Müller counters to ensure a thorough evaluation of background radiation levels in these educational settings. The results show that the detected radiation levels range between \(14 ± 1.22\) and \(26 ± 1.14\) cpm, with an average of \(22 ± 1.32\) cpm. Additionally, the dose rate values in the libraries range between \(0.16 ± 0.02\) and \(0.25 ± 0.03\) \(μ Sv/h\), with an average of \(0.21 ± 0.02\) \(μ Sv/h\). The measurements were conducted in late June and early July 2024, a period of high student concentration due to the proximity of final exams. The facilities of the various libraries span from the ground floor to the third floor, which did not affect the distribution of background radiation measurements. Although factors such as building types or air quality were not considered in this study, these aspects are recognized as relevant and are suggested for future research, which could utilize more sophisticated measurement equipment. This analysis provides a valuable reference for subsequent studies on background radiation in university environments, and the data obtained can be used to compare radiation levels in different contexts and to implement appropriate safety measures to protect students and library staff.